Teachers' Perspectives on the Implementation of the Pancasila Student Profile Strengthening Project (P5) in Madrasah: A Case Study at MA Unggulan Bustanul Hikmah - Amelia Syah Fitriha; Nur Laella Romadhoni; Mohammad Nurwahid (Privietlab, 2026)
This study aims to explore teachers' perspectives on the implementation of the Pancasila Student Profile Strengthening Project (P5) at MA Unggulan Bustanul Hikmah, a leading madrasah (Islamic school) that has implemented the Independent Curriculum. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the Miles and Huberman interactive model. The results showed that teachers' understanding of the P5 concept varied depending on their educational background, teaching experience, and previous training. There were three types of teacher perspectives on P5: optimistic, skeptical, and pragmatic. Despite facing various challenges such as limited conceptual understanding, technical implementation, and institutional support, teachers developed various adaptation strategies, including integrating values ​​into learning, cross-subject collaboration, and continuous reflection and evaluation. These findings emphasize the importance of contextual training, professional mentoring, and systemic support for the effective implementation of P5 and its alignment with the characteristics of madrasah education.